Clinicopathological characteristics and outcomes of colorectal mucinous adenocarcinoma: a retrospective analysis from China - Huang, An; Yang, Yong; Sun, Zhuang; Hong, Haopeng; Chen, Jiajia; Gao, Zhaoya; Gu, Jin (Frontiers in Oncology, 2024)
Background: Mucinous adenocarcinoma (MAC) is a unique subtype of colorectal cancer and its prognostic value remains controversial. This study aimed to compare the clinicopathological characteristics and prognostic differences between patients with MAC and non-mucinous adenocarcinoma (NMAC). Methods: 674 patients with NMAC, 110 patients with adenocarcinoma with mucinous component (ACWM) and 77 patients with MAC between 2016-2019 were enrolled in the study. Univariate and multivariate Cox regression were performed to analyze the factors associated with prognosis. Predictive nomograms of overall survival (OS) and cancer-specific survival (CSS) for patients with colorectal adenocarcinoma were constructed. Confounding factors were eliminated by propensity score matching (PSM). Results: Compared with patients with NMAC, patients with MAC were more likely to have a tumor located at the proximal colon, present with a larger tumor diameter, more advanced T stage, higher frequency of metastasis, deficiency of mismatch repair, and elevatedpositive preoperative carcinoembryonic antigenCEA. Patients with MAC were related to worse OS (HR=2.53, p<0.01) and CSS (HR=3.09, p<0.01), which persisted after PSM. Subgroup analysis demonstrated that patients with left-sided or stage III/IVⅢ/Ⅳ MAC exhibited a comparatively worse OS and CSS than those with NMAC. Furthermore, in patients with stage ⅡII with a high-risk factor and stage III MAC, adjuvant chemotherapy was associated with an improved OS, CSS, and RFS. Conclusion: Compared with the NMAC phenotype, the MAC phenotype was an independent risk factor for poor prognosis in colorectal adenocarcinoma with worse OS and CSS, particularly patients with left-sided colorectal cancer and stage III/IV. However, patients with MAC can still benefit from adjuvant chemotherapy.